The Analysis of Political Discourse in Anies Baswedan Interview with The Sydney Morning Herald - Dhion Meitreya Vidhiasi (LP2M IAIN Sultan Amai Gorontalo, 2020)
Indeed, the political world is never free of whatever smells of controversy. News that is still widely debated is an article in the Australian newspaper, The Sydney Morning Herald, written by James Masolla dated May 7, 2020. The article was a conclusion from his interview with Anies Rasyid Baswedan, Governor of DKI Jakarta. This study aims at analyzing the political discourse contained in the video interview with James Masolla given by Governor Anies by seeing the persuasive strategy used by both people. The data obtained were then analyzed by employing the theory of persuasive strategy. Researchers used descriptive methods to tell the results of the analysis of this study. The findings of this study show that the interview with James Masolla by Anies attracted a lot of different perspectives within the audience. James’ skill in supporting and directing Anies has also earned Anies supporters’ respect for the Governor. The quality of the argument given by Anies is excellent because it can provide a probability claim and provide a desirably claim. This has been shown that the usage of the persuasion approach allows clarifying the meaning behind an argument. Persuasive techniques may also be utilized to forecast the reaction and the behavior the interlocutors want. There is potential for what Anies did to guide him in the contestation of the presidential election in 2024, although it is still too early to talk about it. Anies’ interview, however, showed that there was a problem between DKI Jakarta’s provincial Government and the national Government.